The Effect of Government Expenditures, Private Investment and Labor on Economic Growth in Pidie District - Munzir AG; Mohd. Nur Syechalad; Vivi Silvia (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study aims to determine the effect of government spending, private investment, and labor on economic growth in Pidie District, Data analyzed from 2000-2016, using multiple linear regression model. The results of research on government spending, private investment and labor both simultaneously and partially have a positive and significant impact on economic growth in Pidie District. Variations of government expenditure variables, private investment and labor are able to explain the variation of economic growth in Pidie District by 48,7 percent and the rest of 51,3 percent influenced by other variables. Labor is the most dominant variable of influence on economic growth in Pidie District. Private investment is the least influence variable to economic growth in Pidie District. The need for a policy that could make private government investment spending, and labor increases simultaneously so it is likely to have a positive impact on improving economic growth in Pidie District.